Kajian Arkeologi Kota Kulit Kerang Pengkalan Bharu, Perak, Malaysia - Mohamad Hanif B. Hj. Md. Noor (Berkala Arkeologi Sangkhakala, 2010)
AbstractArchaeological sites of Pengkalan Bharu, Perak is one of the important ports in Malaysia. The port is associated with the center of the Government of New Beruas. Establishment of the port city is to anticipate the enemy like a pirate attack of Siam, Aceh, Majapahit, Selangor and Portuguese.